2016
DOI: 10.1038/bonekey.2016.2
|View full text |Cite
|
Sign up to set email alerts
|

Sclerostin serum levels in patients with systemic autoimmune diseases

Abstract: Systemic autoimmune diseases (SADs) are associated with lower bone mass and an increased risk of fractures. Sclerostin has a pivotal role in bone metabolism. Available data on circulating sclerostin levels in healthy subjects are limited, whereas those in SAD patients are absent. Our objective was to determine circulating sclerostin concentrations in systemic lupus erythematosus (SLE), systemic sclerosis (SSc) and Crohn's disease (CD) patients, and to analyze the factors associated with sclerostin concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
1
8
1
Order By: Relevance
“…In the present study, the sclerostin levels were significantly higher in our SLE patients than in controls. This result was inconsistent with that in the study of Fernández-Roldán et al, 14 the only available study conducted on SLE patients, who found that SLE patients did not differ from healthy controls regarding sclerostin levels. They conducted their study on a relatively smaller sample size and did not clarify the demography of their cohort 14 …”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…In the present study, the sclerostin levels were significantly higher in our SLE patients than in controls. This result was inconsistent with that in the study of Fernández-Roldán et al, 14 the only available study conducted on SLE patients, who found that SLE patients did not differ from healthy controls regarding sclerostin levels. They conducted their study on a relatively smaller sample size and did not clarify the demography of their cohort 14 …”
Section: Discussioncontrasting
confidence: 98%
“…It was found to have a negative effect on bone mineral density (BMD) in postmenopausal women 41 . In SLE patients, Fernández-Roldán et al 14 showed a positive correlation between sclerostin levels and T and Z score values of BMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In partial contrast, a study which evaluated changes in sclerostin levels following exogenous glucocorticoid initiation found no significant change in serum sclerostin levels after two months of therapy, but a slight increase in sclerostin levels relative to baseline when assessed at 12 months (P=0.045) [54]. In addition, in a heterogeneous population of patients with systemic autoimmune diseases, Fernandez-Roldan et al [55] found no effect of glucocorticoid treatment on serum sclerostin levels. Reasons for these seemingly discrepant results are unclear, although one potential explanation is that sclerostin measurements in the various studies were done using different assays.…”
Section: Hormonal Regulation Of Sclerostinmentioning
confidence: 99%
“…Notably, they found that the SOST levels were lower than the baseline after 4 weeks. A recent study of patients with SLE, systemic sclerosis, and Crohn's disease revealed some heterogeneity in SOST levels between different autoimmune diseases . Thus, the discrepancies among recent studies may be partly due to nonlinear changes in SOST levels and the underlying diseases.…”
Section: Discussionmentioning
confidence: 99%